Are we running out of exhaustible resources? - Pretis, F; Hepburn, C; Pfeiffer, A; Teytelboym, A (Elsevier, 2023)
Mineral and material commodities are essential inputs to economic production, but there have been periodical concerns about mineral scarcity. However, there has been no systematic recent study that has determined whether mineral commodities have become scarcer over the longer run. Here we provide systematic evidence that worldwide, near-term exhaustion of economically valuable commodities is unlikely. We construct and analyse a new database of 48 economically-relevant commodities from 1957–2015, including estimates of worldwide production, reserves and reserve bases, prices, and production, using publicly-available data and further data requested from the United States Geological Survey. We explore trends in prices, reserves-to-production ratios, and production itself, on a commodity-by-commodity basis, using econometric techniques allowing for structural changes, and further estimate overall trends robust to outlying observations. For almost all commodities, we cannot reject the null hypothesis of no trend in prices and exhaustion, while production has increased. Price signals appear to have guided consumption and provided incentives for innovation and substitution. Concerns about mineral depletion therefore appear to be less important than concerns about externalities, such as pollution and conflict, and ecosystem services (e.g. climate stability) where price signals are often absent.